2020
DOI: 10.1002/app.48977
|View full text |Cite
|
Sign up to set email alerts
|

Excellent oil/water separation performance of poly(styrene‐alt‐maleic anhydride)/fluorocarbon surfactant membrane filter with functionalized multiwalled carbon nanotubes

Abstract: Polymer/fluorocarbon surfactant membranes have been reported to display excellent oleophobic/hydrophilic behavior and outstanding oil/water separation properties. In this work, multiwalled carbon nanotubes (MWNTs) enhanced poly(styrene‐alt‐maleic anhydride)/fluorocarbon surfactant (PSMA/MWNTs/FS) membrane filters were prepared by dip‐coating PSMA/MWNTs/FS on stainless steel meshes for efficient oil/water separation. The microstructure, thermal properties, wettability, oil/water separation ability, and recyclab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 75 publications
(138 reference statements)
0
4
0
Order By: Relevance
“…During the 20 cycles of reuse in hexane–water separation, the oil rejection rate was maintained over 99% (Figure b), and the average water flux of the PMAA-grafted mesh was 51,423 ± 1176 L m –2 h –1 (Figure S6). It is noted that the grafted mesh was reused with no mesh cleaning, which was reported to regenerate oil–water separation meshes and restore the water flux. ,, Compared with the reported reuse of hydrophilic meshes (Table S1), the PMAA-grafted meshes demonstrated a flux decay of 2.7% after 20 cycles of oil–water separation. As for the PMAA-crosslinked mesh, not only the water flux was much lower, but the hexane rejection also dropped below 97% at cycle 7, and the mesh completely lost the separation capability at cycle 11 (Figure b).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…During the 20 cycles of reuse in hexane–water separation, the oil rejection rate was maintained over 99% (Figure b), and the average water flux of the PMAA-grafted mesh was 51,423 ± 1176 L m –2 h –1 (Figure S6). It is noted that the grafted mesh was reused with no mesh cleaning, which was reported to regenerate oil–water separation meshes and restore the water flux. ,, Compared with the reported reuse of hydrophilic meshes (Table S1), the PMAA-grafted meshes demonstrated a flux decay of 2.7% after 20 cycles of oil–water separation. As for the PMAA-crosslinked mesh, not only the water flux was much lower, but the hexane rejection also dropped below 97% at cycle 7, and the mesh completely lost the separation capability at cycle 11 (Figure b).…”
Section: Resultsmentioning
confidence: 94%
“…Consequently, the obstruction of pore openings led to the reduction of water flux, 19,32,34 and the water flux continued to decrease with the repeated use in oil−water separation. 19,33,35 To implement oil−water separation meshes in industrial applications, where large volumes of oily wastewater need to be deoiled, 36,37 further study is essential to investigate how to maximize water flux while accomplishing high oil rejection rates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it has been found that SDS has a strong influence on the formation of SiO 2 spherical films at different concentrations [ 19 , 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%